Settling the Office: The Australian Prime Ministership from Federation to Reconstruction. (September 2016) - Day, David
Abstract : Settling the Office: The Australian Prime Ministership from Federation to Reconstruction. By Paul Strangio, Paul 't Hart and James Walter (Melbourne: Melbourne University Publishing, 2016), pp. vi + 312. Thirty‐two illustrations. AU49.99 (cloth).